Partisipasi Masyarakat dalam Pengelolaan Waduk Amburan sebagai Sumber Pemenuhan Kebutuhan Air di Desa Kandangan, Gresik - Indah, Fadia; Ma'ruf, Muhammad Farid (Universitas Negeri Surabaya, 2024)
This research is intended to analyze community participation in the management of the Amburan reservoir as a source of meeting water needs in Kandangan Village, Gresik Regency. Furthermore, the research aims to explore the management process of the Amburan reservoir which is utilized in the form of independent self-help PAMSIMAS. As for the management of the reservoir, it is still not optimal, there are obstacles, namely when the dry season is prolonged, the water quality becomes cloudy and the reservoir recedes which has an impact on water availability. This research uses a qualitative approach descriptive analysis technique through indicators of community participation according to Cohen and Uphoff cited by Dwiningrum (2011) which includes participation in decision making, implementation, utilization, and evaluation. The data collection used through observation, interviews, and documentation then analyzed through data reduction, verification, and conclusion drawing. The results showed that the Amburan reservoir management activities through community participation were shown in the program planning process through initial idea discussions, then in the implementation of the community was willing to fund this program. The existence of reservoir management through the construction of PAMSIMAS provides benefits to the community because they can meet their water needs. The level of community awareness in attending evaluation meetings is still low and not well scheduled. So, supervision of the running of the program is also necessary. The suggestions for the village government and the management team can create a non-formal forum starting from a small forum between neighbourhood associations so that the community is willing to convey their responses, suggestions, or criticisms. Then conduct counselling to the community regarding the importance of managing water resources.